(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
Bone age is the degree of maturation of a person’s bones. As a person grows from foetal life through childhood, puberty, and finishes growth as a young adult, the bones of the skeleton change in size and shape. Long bone growth takes place at the epiphyseal or growth plate, located between the metaphysis and epiphysis. Age estimation is indispensable in civil and criminal cases, where there is no document available to certify the age, especially in developing countries like India. There are various methods for age estimations, like dental examination, general physical examination X ray examination of various bones etc. X ray examination of bones especially for ossification and the union of epiphyses give relatively reliable results. As there are different criminal laws to deal with minors in conflict with law and age of sexual assault victim is also crucial as different clause applies for minors. Courts totally depend on medical report for age provided by board of doctors. It is thus there is huge responsibility on the doctors to be accurate with least degree of error. Keeping accuracy in the mind the present study was undertaken. X-rays of all cases were studied and divided among 4 categories (Degree 0- Degree 3) depending on the status of fusion of long bones, 100% of males complete fusion at distal end of femur at the age group of 17-18, Proximal end of tibia at the age group of 17-18, proximal end of fibula at the age group of 18-19 , distal end of tibia at the age group of 16-17 and distal end of fibula at the age group of 16-17 .